Personalized treatment of patients with muscular-joint dysfunction of the temporomandibular joint on the background of post-traumatic stress disorder - Khomiak , Kateryna; Kostiuk, Tetiana; Proshchenko , Nina (The Ukrainian Scientific Medical Youth Journal, 2023)
dysfunction of the temporomandibular joint (TMJ) is a common disease with a multifactorial etiology. Often, the disease acquires a psychosomatic nature, so patients in the anamnesis note the presence of stress, sleep disturbances, headaches, chronic fatigue and irritability. During the period of active hostilities and the difficult political, socio-economic situation in Ukraine, the number of patients with post-traumatic stress disorder (PTSD) is increasing. The current foreign political situation of Ukraine has an impact on people tend to depressive disorders, which subsequently causes changes in the human body in general, specifically in the musculoskeletal complex of the TMJ. The aim of the study is to study and compare the manifestations of TMJ dysfunction in patients with established post-traumatic stress disorder (PTSD) and to evaluate the effectiveness based on the analysis of a multidisciplinary approach in the treatment of the disease. A total of 42 patients (28 men and 14 women) with TMJ musculoskeletal dysfunction were examined. To identify the degree of severity of muscle and joint dysfunction, such materials and methods were used as: general clinical (examination of the oral cavity, physical methods of studying dentognathic anomalies, analysis according to Helkimo (2014) and additional (questionnaire)), statistical methods of numerical data. For the treatment of PTSD - specialized psychological (cognitive-behavioral therapy (CBT), EMDR-therapy ("Eye Movement Desensitization and Reprocessing") and group psychotherapy). The priority of this study was a comparative assessment of the condition of patients who received multidisciplinary treatment. In the course of the study, a clear connection and influence of PTSD on the clinical manifestations of TMJ dysfunction was revealed. It has been found that patients with musculoskeletal dysfunction usually experience post-traumatic stress disorder, while patients with PTSD also have a higher prevalence of musculoskeletal dysfunction.It was established that patients who were treated with the involvement, first of all, of a psychologist, showed a 2.4-fold reduction in TMJ dysfunction. Thus, a detailed anamnesis and taking into account psychological disorders by 73% (р<0.05) allow to achieve success in the management of patients with TMJ dysfunction on the background of PTSD. An algorithm for personalized management of patients with TMJ dysfunction on the background of PTSD was developed with the involvement of a psychologist. A multidisciplinary approach to the specified symptom complex allows to improve the diagnosis and treatment results of this severe category of patients.